PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTU MEDIA AUDIO VISUAL UNTUK MENINGKATKAN BERPIKIR KRITIS KELAS 4 SD - Susilowati, Rini (Universitas Pendidikan Ganesha, 2018)
This type of research Â is a class action research. The purpose of this research enhances students ' critical thinking ability by application of Problem Based Learning with Â Audio Visual Media. Data were collected by using a sheet of observation and evaluation tests. The average percentage of critical thinking ability of students overall observation sheet on precyae 13.8% increase in cycle cycle I 69% and increased again in cycle II 96.5%. And the overall percentage on the test results the evaluation cycle I 44.8% increase in cycle II 96.6%. Thus the results showed that the application of problem based learning with audio visual media is able to enhance the critical thinking ability of students.